TECHNICAL EFFICIENCY OF LEISA SYSTEM SHALLOT FARMING IN BANTUL REGENCY - Lantarsih, Retno; Perdana, Putri; Wijayanti, Irene Kartika Eka; Hasanah, Erni Ummi (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Implementing the Low External Input Sustainable Agriculture (LEISA) concept is expected to optimize the use of local inputs, reduce negative environmental impacts, and produce safe products. In Bantul Regency, a group of shallot farmers have cultivated using the LEISA system, but their production has decreased. This research aims to determine factors that influence production, the influence of technical inefficiency on production variability, sources of inefficiency, and the level of technical efficiency of LEISA system shallot farming. This research is quantitative descriptive. Determining the research location used the purposive method and selecting the sample using random sampling techniques. Technical efficiency analysis uses the Cobb Douglas Stochastic Frontier production function. The research results show that land area positively affects shallot production in the LEISA system with a regression coefficient of 0.718. Technical inefficiency problems that farmers can control contribute 1% to production variability, and technical inefficiency originates from farmer age. LEISA system shallot farming in Bantul Regency is not technically efficient. This research implies that farmers can increase LEISA system shallot production by increasing the land area, and to increase technical efficiency, this can be done by increasing farmer experience and increasing the motivation of young farmers in LEISA system shallot farming. Farmers with experience and who are young have better physical and decision-making abilities. Apart from that, further research must be conducted to evaluate the sustainability of the LEISA system shallot farming.